Negotiating health and autonomy: Data exclusivity, healthcare policies and access to pharmaceutical innovations - Henrique Zeferino de Menezes; Julia Paranhos; Ricardo Lobato Torres; Luciana Correira Borges; Daniela de Santana Falc\~ao; Gustavo Soares Felix Lima (South Centre, 2024)
This paper analyzes the debate over the international dissemination of data exclusivity as a form of protection for clinical trial data. This is a critical demand for pharmaceutical companies seeking larger market shares and longer periods of monopoly in order to recover investments in research and development and greater profitability. However, this is a sensitive issue with economic and social repercussions for developing countries that adopt this protection regime. This paper highlights critical issues for the political economy of innovation and presents a review of empirical studies that show that data exclusivity delays the entry of generic drugs into the market, increasing prices and reducing access. At the same time, its adoption has no benefits because there are no positive effects on internal technological innovation, nor reduction of the "International drug lag", nor the development of drugs for specific epidemiological demands.
Keywords: 300; Access to Medicines; Clinical Trials; Data Exclusivity; Generic Medicines; Health; Healthcare; Innovation; Intellectual Property; Pharmaceuticals; Research and Development (R&D); Test Data; Test Data Protection; TRIPS; TRIPS Agreement